Diagnosis of Levator Ani Muscle Avulsion in Instrumented Delivery: Meta-analysis - José Antonio García-Mejido; Ana Fernández-Palacín; Carolina Lao-Peña; José Antonio Sainz-Bueno (IMR Press, 2022)
Objective: The objective of this meta-analysis was to establish the rates of levator ani muscle (LAM) avulsion in patients after forceps delivery (FD) and vacuum delivery (VD) as assessed by 3D/4D transperineal ultrasound. Methods: A systematic search was performed in the MEDLINE, PubMed, Google Scholar, and Embase databases up to December 31, 2021. Studies that studied primiparous women diagnosed with LAM avulsion by 3D/4D transperineal ultrasound in VD or FD were included. To do the meta-analysis, the jamovi project program version 2.2 (2021) was used. Results: The search yielded 1225 studies that met the MeSH criteria, of which 26 were included in the review. The estimated joint OR for VD vs. normal vaginal delivery (NVD) was 1.93 (95% CI: 1.31-2.86), for FD vs. NVD was 5.33 (95% CI: 3.78-8.11), and for FD vs. VD was 2.36 (95% CI: 1.46-3.84). Conclusions: Instrumented delivery with forceps or vacuum favors LAM avulsion. It is not possible to establish whether this injury is attributable to the specific instrument or to the type of delivery involved in the instrumentation itself.